The Implementation Of Feedback In Means-Ends Analysis Of Student's High-Level Mathematic Thinking Ability - Mei Astuti; Kartono Kartono; Nuriana Rachmani Dewi (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2022)
This research goals is to apply learning by using the Means-Ends Analysis model with direct corrective feedback to hope that higher-order thinking skills and students' self-efficacy can increase. Researcher used mixed method with sequential designs. Result of this research obtained means-ends analysis with a quality direct corrective feedback on achievement of learners’ higher order mathematical thinking skill. This research population was class VIII MTs Ma'arif 20 Kalidadi in the first Semesters for the 2020/2021 Academic Year. Sampling using cluster random sampling technique, which is randomly selected two classes from the population. Higher order thinking ability with high self-efficacy category shows that subject 1 has shown that answer has reached indicators of analyzing then evaluating but has not seen achievement of indicator of creativity.High-order thinking skills with moderate self-efficacy category indicate that subject 2 has shown that the answer had reached the indicators of analyzing and evaluating but has not seen achievement of indicators of creativity; Higher order thinking skills with high self-efficacy category indicate that subject 3 does not show the answer, has reached the indicators of analyzing, evaluating then creating and at evaluation stage there is no correct answer to complete answer to the end. This can also be seen in the interview stage which shows that subject 3 cannot give the right reason.